ENHANCING STUDENTS’ ECOLOGICAL COMPETENCE THROUGH CONTEMPORARY EDUCATIONAL APPROACHES - Jamolovna, Pulatova Gulruh (PT. Antis International Publisher, 2025)
Objective: This study examines the relevance of ecological problems in both global and national contexts, particularly under the conditions of globalization, and explores effective educational mechanisms to address these issues. Method: The research employs a scientific analysis of current ecological challenges and evaluates educational strategies, including competency-based education, interactive techniques, project-based learning, and a